Perancangan Sistem Akuntansi dan Penjualan Berbasis Web pada Griya Teknik Elektro - Martono (Jurnal PROCESSOR, 2023)
Griya teknik elektro is a shop engaged in the supply of goods and services to repair engineering and electrical equipment. Currently, in carrying out transactions and processing financial reports, they still use paper media as the main option for storing transaction data and storing information, which ultimately causes difficulty in finding data and the high costs required to run their business. Because of this, the authors decided to carry out research entitled design of web-based accounting and sales systems at griya teknik elekto with the intention that all the problems faced by them both in the transaction process to report processing can be resolved. The accounting and sales systems contained in this study are described in the form of modeling use case diagrams along with class diagrams. The final product of this research is a web-based accounting and sales system that allows users to perform various data processing such as managing accounting such as customer ledgers and supplier ledgers, managing attributes such as brands, cities and stores, managing customers such as customer data and customer payments. , managing inventory such as products, categories and stocks, managing reports such as sales reports and return reports, managing purchase lists, managing purchase returns and changing passwords and also login and logout from the system.